Role of membrane fouling substances on the rejection of N-nitrosamines by reverse osmosis. (1st July 2017) - Fujioka, Takahiro; Kodamatani, Hitoshi; Aizawa, Hidenobu; Gray, Stephen; Ishida, Kenneth P.; Nghiem, Long D.
Abstract: The impact of fouling substances on the rejection of four N -nitrosamines by a reverse osmosis (RO) membrane was evaluated by characterizing individual organic fractions in a secondary wastewater effluent and deploying a novel high-performance liquid chromatography-photochemical reaction-chemiluminescence (HPLC-PR-CL) analytical technique. The HPLC-PR-CL analytical technique allowed for a systematic examination of the correlation between the fouling level and the permeation of N -nitrosamines in the secondary wastewater effluent and synthetic wastewaters through an RO membrane. Membrane fouling caused by the secondary wastewater effluent led to a notable decrease in the permeation of N -nitrosodimethylamine (NDMA) while a smaller but nevertheless discernible decrease in the permeation of N -nitrosomethylethylamine (NMEA), N -nitrosopyrrolidine (NPYR) and N -nitrosomorpholine (NMOR) was also observed. Fluorescence spectrometry analysis revealed that major foulants in the secondary wastewater effluent were humic and fulvic acid-like substances. Analysis using the size exclusion chromatography technique also identified polysaccharides and proteins as additional fouling substances. Thus, further examination was conducted using solutions containing model foulants (i.e., sodium alginate, bovine serum albumin, humic acid and two fulvic acids). Similar to the secondary wastewater effluent, membrane fouling with fulvic acid solutions resulted in a decrease in N -nitrosamine permeation. In contrast, membrane fouling with the other model foulants resulted in a negligible impact on N -nitrosamine permeation. Overall, these results suggest that the impact of fouling on the permeation of N -nitrosamines by RO is governed by specific small organic fractions (e.g. fulvic acid-like organics) in the secondary wastewater effluent. Graphical abstract: Highlights: Effects of fouling substances on N -nitrosamine permeation through RO were evaluated. N -nitrosamines permeating through RO decreased by fouling with secondary effluent. Fouling with fulvic acid also reduced the permeation of N -nitrosamines. Fouling with other model foulants did not influence the permeation of N -nitrosamines. Fulvic acid-like substances were attributed to a decrease in N -nitrosamine permeation.